Avaliação do potencial mutagênico da água do açude de Lucrécia (RN- Brasil): um enfoque na relação saúde e ambiente - Garcia, Anuska Conde Fagundes Soares (2011)
The water quality of many reservoirs in the world has been reduced due to percolation of contaminants to water, which can have natural or anthropogenic origin, increasing the level of genotoxic compounds in aquatic ecosystems. This fact has contributed to the reduction of environmental quality, and commitment the health of living beings that inhabit these ecosystems, including the human population. In this backdrop of reduced water quality, is the Lucrecia dam, which is a major surface water reservoirs by volume of semi-arid region of Rio Grande do Norte, and that has shown contamination by heavy metals, cyanobacteria toxic and the natural presence of Radon. The population that use this source has been showing high rates of cancer, popularly associated with the consumption of this water, with a prevalence about three times higher compared to the whole state of Rio Grande do Norte. Based on this, the present study aimed to evaluate the mutagenic potencial of surface water from the Lucrecia dam, using the Micronucleus Test in Tradescantia pallida (Trad-MN) and in human peripheral blood lymphocytes (CBMN) assay, as well as identify the concentrations of some heavy metals in this water. Water samples were collected on a dry season and a rainy season, in two distinct points. Moreover, in order to bring a completely view about the relationship of man-health-environment in this local, through the knowledge of knowing / acting environmental from residents of Lucrecia, and the use and perceptions they have about the dam of your city, a study of Environmental Perception was carried out with local residents. The results obtained for the both micronucleus test, showed significant results for the three points analyzed. The strongest mutagenic effect was observed in the dry season for both assays. Chemical analyses detected an increase of heavy metal levels in different points and season above the maximum allowed by legislation. Regarding the study of Environmental Perception with local residents, it was observed the knowledge of the environment that the residents have, as well as the strong ties and perceptions with the dam of the city. Thus, the combination of these two aspects (the genetic toxicity tests conducted in the dam together with analysis of environmental perception with the residents of Lucrecia) allowed to draw a more complete diagnosis on the local situation